CEO inside debt, market competition and corporate risk taking. Issue 4 (8th April 2019) - Sheikh, Shahbaz
Abstract : Purpose: The purpose of this paper is to investigate the effect of market competition on the relation between CEO inside debt and corporate risk-taking. Design/methodology/approach: Ordinary least squares regressions are used to estimate the relation between CEO inside debt and firm risk. Additionally, instrumental variable (IV-GMM) regressions are used to check the robustness of the results. Findings: The results of this paper indicate that CEO inside debt is negatively associated with the measures of future risk. However, this negative association is influenced by market competition. Specifically, CEO inside debt results in lower levels of firm risk when market competition is high. When market competition is low, inside debt has no effect on firm risk. Additional results show that CEOs with large inside debt tend to decrease R&D investments and financial leverage and increase firm cash holdings and working capital only when market competition is high. Overall, these results suggest that market competition significantly influences the effect of CEO inside debt on corporate risk-taking by changing the strength of incentives from inside debt. Practical implications: CEO inside debt could be used to provide incentives to CEOs to manage corporate risk-taking. Social implications: The empirical results in this paper provide a practical tool to the boards of corporations to manage corporate risk-taking. The results suggest that boards can reduce excessive risk-taking by increasing the level of debt type compensation incentives. However, this strategy is effective only when market competition is high because in such markets inside debt provides the strongest incentives to reduce corporate risk. When competition is low, incentives from inside debt are ineffective in managing corporate risk-taking. Originality/value: This is the first study that shows that the negative association between CEO inside debt and corporate risk-taking critically depends on the intensity of market competition.